Benefits of the kangaroo method for low weight newborn babies: An integrative review (Research, Society and Development, 2023)
The Kangaroo Method is a neonatal intervention aimed at qualified and humanized care for premature newborns. The objective is to present the benefits of the kangaroo method for low birth weight neonates. Integrative literature study. Data collection took place from May to July 2022. Using the Ministry of Health (MS) Manual and databases from the Brazilian Library of Theses and Dissertations (BDTD), Scientific Electronic Library Online (SicELO), Google Scholar and Latin American and Caribbean Literature on Health Sciences (LILACS) using terms and descriptors such as kangaroo care, benefits, low birth weight newborns. Original articles published in full, available online and free of charge, in Portuguese, from the last five years (2017 to 2022) were selected and articles unrelated to the research objectives were excluded by reading the title and abstract. After the identification of the articles on that theme, an exploratory reading was carried out in order to verify if the articles are consistent with the theme. Then, a thorough reading was carried out for analysis and further discussion.